The Impact of Vessels on Humpback Whale Behavior: The Benefit of Added Whale Watching Guidelines - Currie, Jens J.; McCordic, Jessica A.; Olson, Grace L.; Machernis, Abigail F.; Stack, Stephanie H. (Frontiers in Marine Science, 2021)
The concurrent increase in marine tourism and vessel traffic around the world highlights the need for developing responsible whale watching guidelines. To determine the impact of vessel presence on humpback whale behaviors in Maui Nui, a land-based study was conducted from 2015-2018 in Maui, Hawaii. Theodolite tracks were used to summarize humpback whale swim speed, respiration rate, dive time, and path directness to determine the potential impacts of various types of vessel presence on whale behavior. Vessel presence, proximity, and approach type in conjunction with biological parameters were used in a generalized additive modeling framework to explain changes in whale behaviors. The results presented here show increases in swim speed, respiration rate, and path directness in conjunction with decreasing dive times, which has been shown to be an energetically demanding avoidance strategy. These observations, in conjunction with increasing awareness on the implication of non-lethal effects of human disturbance and changing oceanic environments on humpback whales, highlights the need for a precautionary approach to management. Stricter guidelines on whale watching will limit the level of disturbance to individual humpback whales in Hawaii and ensure they maintain the fitness required to compensate for varying ecological and anthropogenic conditions.